P-774 Risks management in a donor program: application of Failure Mode and Effect Analysis from gamete matching to gamete thawing. (30th June 2022) - Esposito, S; De Santis, L; Rabellotti, E; Privitera, L; Biancardi, R; Sarais, V; Viganò, P; Candiani, M; Papaleo, E; Alteri, A
Abstract: Study question: Is failure mode and effects analysis (FMEA) a useful and effective method of risk assessment in a gamete donor program? Summary answer: The analysis of the potential failures, their causes and effects significantly improved the safety strategies previously adopted in our gamete donor program. What is known already: At present, in Italy, the donation of fresh gametes is possible, but almost unmanageable due to the lack of donors and the refund to donors forbidden by law. As a result, many IVF Italian Centers established agreements with foreign gametes cryo-banks in order to meet the huge demand for donation treatments. The exchange of personal sensitive data and gametes between the sending and receiving centers represents a crucial aspect in a donor cycle. Each stage of this process, from gamete request to gamete thawing, is not error-free. FMEA represents a strategy to identify and mitigate potential failures before they occur. Study design, size, duration: Fifty-eight oocyte and 4 sperm donation cycles were performed at our IVF facility from September 2019 to January 2021. Gametes came from a single Spanish cryo-bank. FMEA represents a proactive risk evaluation tool useful to identify real or potential failures and to develop actions to minimize risks. FMEA was conducted, in January 2021, by a team consisting of 2 gynaecologists, 3 embryologists and 2 quality managers and repeated 8 months later. Participants/materials, setting, methods: Processes were analyzed to identify and score the potential failure modes using the risk priority number (RPN) scoring system. The calculation has been obtained by multiplying 3 factors: severity, occurrence and detectability scored from 1-5. After calculating the criticality of each failure mode, an action plan was prepared and then effectiveness of new process was monitored. Finally, FMEA was repeated and the improved RPN after the corrective actions was calculated. Main results and the role of chance: In our gamete donation program, we mapped four phases: gamete request, donor-recipient matching, gamete delivery and gamete thawing. All the steps presented multiple failures and 11 different potential failure modes had been identified. Failure modes as the incorrect transcription of the recipient data, the acceptance of a donor proposal not well-matched with recipients and the receipt of gametes unsuitable for the couple correlate to high-risk scores with 30 RPN. These events may have severe consequences such as an incorrect matching between donor and recipient, and the subsequent birth of a child from a mismatched donor. Although gamete request, donor-recipient matching and receiving gametes phases are mainly characterized by document checking, the introduction of witnessing by another physician or embryologist, reduced the risk by 50%. Therefore, the introduction of double checking by a second operator represents an essential control measure to avoid errors. Limitations, reasons for caution: This study is influenced by the general limitations of the FMEA approach, such as different personal experiences and skills of the participants since failures may be unrecognized, underestimated or overstated. Wider implications of the findings: Performing a risk assessment in a donor program represents a valid strategy to mitigate risks of incorrect matching and loss of traceability. Since errors in data record and acceptance of donor proposal may cause important down streaming consequences, the double witnessing is strongly encouraged. Trial registration number: NA